The Effectiveness Analysis of Joint Use of Different Groups Anti-Inflammatory Drugs Treatment and Prevention of Cystoid Macular Edema in Patients after Phacoemulsification - Yu. I. Pirogov; A. Yu. Bovykina (Oftalʹmologiâ, 2018)
Purpose: to analyze the results of the joint eye drops application of 0.09 % solution of bromfenac and 0.1 % solution of dexamethasone and subtenons triamcinolone injection for treatment  and prevention of cystoid macular edema (CME) in patients after phacoemulsification.Patients and methods: The study included 914 patients (1147 eyes) which held phacoemulsification with IOL implantation. Depending on the postoperative treatment patients randomized into  two groups. Patients of the first group received instillation of eye  drops of antibiotics-fluoroquinolones and 0.1 % dexamethasone.  Patients of the second group were prescribed instillation of eye drops of 0.09 % solution of bromfenac in addition to the treatment. In  each group the patients diagnosed CME after phacoemulsification  were divided into subgroups depending on the presence or absence  of concomitant involution of retinal pathology. In cases of diagnosis of macular edema after phacoemulsification (2nd group of  patients) periocular triamcinolone injections were made.Results. The efficacy of bromfenac was estimated by the number of  cases of postoperative CME in the compared groups. In patients of  the first group, complications occurred in 3.1 % of cases. In patients  of the second group the number of complications was  significantly lower (1.5 %), including a significant reduction in the  incidence of CME observed in patients without concomitant of  macular pathology (AMD and epiretinal fibrosis). A combination of  steroid and NSAID in the treatment of CME provides the regression  of macular edema in all patients, regardless of the presence of  involution macular pathology. The positive effect of periocular  triamcinolone injections in the treatment of anti-inflammatory eye drops was noted in 8 of 9 cases a month after the first injection.